Inflammatory myofibroblastic tumor of right leg and calcified fibroadenoma of left breast removed from a postmenopausal-women: a rare case report and review of literature - Shah, Prachi A.; Kavthiya, Jaydip R.; Prajapati, Bijal (International Surgery Journal, 2023)
Inflammatory myofibroblastic tumors are uncommon neoplasms; presentation of these tumors in the lower extremities is extremely rare. Treatment varies depending on type, location and patient factor. Here the case of 60-year-old female post-menopausal (P2L2) presented with swelling over anterior aspect of right leg which was exophytic in nature and left breast lump. Combined histopathology and immunohistochemistry findings favoured myofibroblastic tumor of borderline category- inflammatory myofibroblastic tumor. Mammography of left breast showed presence of fibroadenoma at 12 o’ clock position. Patient underwent wide local excision of right leg swelling followed by split thickness skin grafting and excision of left breast swelling (lumpectomy). Inflammatory myofibroblastic tumors are of varied biologic potentials. They are generally classified as tumours of intermediate biological activity with uncertain malignant potential. There are many factors which affect treatment and prognosis of the patient. Five types of standard treatment for sarcoma are used: surgery, radiation therapy, chemotherapy, targeted therapy, immunotherapy. Fibroadenomas are benign breast neoplasms, typically present in women from ages of 20-35 years old (premenopausal).